LOW DOSE EFFECTS OF CADMIUM AND LEAD ON GROWTH IN FINGERLINGS OF A VEGETARIAN FISH, GRASS CARP(CTENOPHARYNGODON IDELLA). - M. S. Ahmed; K. S. Ahmed; R. Mehmood; H. Ali; W. A. Khan (Journal of Animal and Plant Sciences, 2012)
A study was conducted to evaluate the effects of cadmium and lead on growth in the fingerlings of a truly vegetarian fish, grass carp (Ctenopharyngodon idella).  Single breed fingerlings (12.0 ± 1.25 cm) of grass carpwere obtained from a commercial fish seed hatchery recommended for good quality of fish seeds. Five treatments groups (T1-T5) in triplicate each containing 50 fingerlings of grass carp were maintained at 24 ± 0.25°C, DO 7.18 ± 0.24 mg/l, pH 6.7 ± 0.22 and hardness 140.7 ± 3.8 mg/l in 90 liters of water in glass tanks. A zero dose treatment (T 1) was maintained as control. While other fingerlings were exposed to 5.0 µg/l (permissible) and 500 µg/l (sublethal) of waterborne cadmium (Cd) as treatment 2 and 3 respectively and 50 µg/l (permissible) and 1000 µg/l (sublethal) of waterborne lead (Pb) as treatment 4 and 5 respectively. Permissible (according to European Union standards for Cd and Pb in drinking water) and sub-lethal concentrations of Cd and Pb were prepared by dissolving cadmium chloride and lead acetate in deionized water. All fish were fed with pelleted green leaf feed (Cd, 0.05 – 0.08 µg/g and Pb, 0.08 – 0.11 µg/g dry weight) to an equivalent of 3 % wet body weight twice daily. Uneaten food and the feces were removed at 30 minutes after feeding from all tanks daily. It was observed that cadmium tiureatments caused significant (p<0.05) reduction in growth as compared to lead treatments and control group. The present studies has revealed that even very low concentrations (permissible) of heavy metals like Cd and Pb, that are considered as safe, do cause effects on growth of a freshwater fish meant for human consumption. It is therefore recommended to take particular precautionary measure to safeguard our water bodies from being contaminated with industrial effluents containing various heavy metal ions.
Keywords: fish growth; grass carp; heavy metal toxicity; permissible dose; sub lethal dose; non-essential heavy metals